TORAKOCHIRURGIAThe detection of EGFR mutations in patients with non-small cell lung cancer in selected molecular diagnostics centers in Poland - Krawczyk, Paweł; Ramlau, Rodryg; Powrózek, Tomasz; Wojas-Krawczyk, Kamila; Sura, Sylwia; Jarosz, Bożena; Walczyna, Beata; Pankowski, Juliusz; Szumiło, Justyna; Dyszkiewicz, Wojciech; Woźniak, Aldona; Milanowski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background: The development of molecularly targeted therapies using epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) has created a need for molecular studies in patients with non-small cell lung cancer (NSCLC). TKIs (gefitinib and erlotinib) show spectacular efficacy in patients with EGFR activating mutations (high response rate with long progression-free survival and improved quality of life). In Poland, despite developments in the field of molecular diagnostics, there is a lack of data concerning not only the frequency of EGFR mutations in NSCLC patients, but also the various molecular techniques for EGFR mutation diagnosis that are being used in different genetic labs. Aim of the study: The aim of this study is to describe the methods for molecular diagnostics of activating mutations in EGFR gene in NSCLC patients from the voivodeships of Lubelskie and Wielkopolskie (Lublin and Greater Poland). Materials and methods : The incidence of EGFR mutations (deletions in exon 19 and substitution L858R in exon 21) was analyzed in 460 patients from the voivodeships of Lubelskie and Wielkopolskie (Lublin and Greater Poland). Results: Adenocarcinoma was diagnosed in 61% of patients, NSCLC NOS (not otherwise specified) in 27%, and large cell carcinoma in 6% of patients. EGFR activating mutations were detected in 10.5% of patients, and were slightly more common in patients with adenocarcinoma (12%) than in those with NSCLC NOS (7.5%) and large cell carcinoma (7%). Mutations occurred slightly more frequently in the material from formaldehyde-fixed paraffin-embedded (FFPE) tissue obtained from NSCLC tumor surgery (12.36%) than in the material from tumor biopsy (8.8%). Materials from surgical resection were reliable for molecular examination significantly more frequently (χ 2 = 10.77, p = 0.001) than the material from biopsy. Furthermore, the postoperative samples provided a higher DNA concentration (p = 0.0002) than the biopsy materials. Conclusions: Molecular diagnosis of EGFR mutations during the qualification process for EGFR-TKI treatment seems justified for all patients with a diagnosis of non-squamous NSCLC, and should be conducted using the most reliable material.